Backstepping Approach for Autonomous Mobile Robot Trajectory Tracking - Ibari Benaoumeur; Benchikh Laredj; Haniﬁ Elhachimi Amar Reda; Ahmed-foitih Zoubir (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper proposes a backstepping controller design for trajectory tracking of unicycle-type mobile robots. The main object of the control algorithms developed is to design a robust output tracking controller. The design of the controller is based on the lyapunov theorem, kinematic tracking controller of an unicycle-like mobile robot is used to provides the desired values of the linear and angular velocities for the given trajectory. A Lyapunov-based stability analysis is presented to guarantee the robot stability of the tracking errors. Simulation and experimental results show the effectiveness of the proposed robust controller in term of accuracy and stability under different load conditions.